Pengaruh Lindi Sampah Perkotaan terhadap Kandungan Kimia Lempung yang Dipadatkan pada Kadar Air yang Berbeda - Yulian Firmana Arifin (Universitas Lambung Mangkurat, 2008)
This research focused on the effect of leachate from municipal waste disposal are (WDA) on the chemical constituents of the clay liner with varies water content. In this research, leachate was taken from Sukolilo WDA and clay for clay liner was taken from Karang Pilang, Surabaya. Clay was compacted with modified Proctor tests. From each of them, samples were prepared at different water content, those are; at optimum water content (wc opt), at wc<wc opt, and at wc>wcopt. Falling head test using 0,005N CaSO4 was carried out. The k value was determined when the hydraulic conductivity was constant. Afterwards, the liquid was replaced with the leachate. Chemical constituents of clay liner were obserbed before and after test. The results show that most of the chemical constituents of clay liner, which permeated by leachate, increase corresponding to the dominant constituent of the leachate. This change is influenced by water content of the clay liner.